The Images of Chinese Female Characters and Chinese Society in Literature Translated from Chinese Into Thai by Her Royal Highness Princess Maha Chakri Sirindhorn - Chen , Xiaomei; Khamchoo, Nattha Khamchoo (Journal of Modern Learning Development, 2024)
This study aims to analyze the images of Chinese female characters and their relationship with Chinese society in the literature translated from Chinese by Her Royal Highness Princess Maha Chakri Sirindhorn. Utilizing a document research methodology, this study conducts a detailed reading and analysis of the images of Chinese female characters, as well as examines their relationship with Chinese society, as depicted in five translated works: “Butterfly,” “Small Village of the Bao Clan,” “What Love is Not Painful,” “Naree Nakara,” and “Emerald.” The findings indicate that the images of Chinese female characters can be divided into three periods: (1) The portrayal of Chinese female characters during the Cultural Revolution, including traditional Chinese women, Chinese women fluctuating between old and new ideas, and Chinese women who are patriotic and loyal to the Communist Party; (2) The portrayal of Chinese female characters during the Cultural Revolution period, including Chinese women who adhere firmly to their ideologies and those who act out of self-interest; and (3) The portrayal of Chinese female characters after the Cultural Revolution, including self-reliant Chinese women and those who sacrifice for their families. These images relate to Chinese social and cultural aspects such as traditions, which include adherence, adaptation, and challenges to traditions; socio-economic conditions, which include adaptation and response to social challenges; and the changing roles and perceptions of women in society, which include changing views on women’s roles and facing social challenges, reflecting the values ​​and lifestyles of women in different eras of Chinese society, from pre-Cultural Revolution to the reform and opening-up era.